The Effect of Location and Shape of Vortex Generators on Aerodynamic Characteristics of a NACA 4415 Airfoil - Abed, Khuder N. (Al-Nahrain Journal for Engineering Sciences, 2023)
This study examines the flow behavior and lift coefficient variations of a NACA 4415 airfoil using different vortex generator configurations. Experimental investigations are conducted in a subsonic wind tunnel at a Reynolds number of 1.8 x 105. The airfoil is tested with two types of vortex generators, namely the dome vortex and the convergent-divergent vortex, positioned at 10%, 28%, and 60% chord locations. Experimental lift coefficients are compared with Airfoil Tools database, showing consistent agreement within an angle of attack range of 0 to 18 degrees. At small angles of attack (0 to 8 degrees), the lift coefficients of the NACA 4415 airfoil with the dome vortex at 10%, 28%, and 60% chord positions are lower compared to the baseline configuration. However, beyond 14 degrees, the highest lift coefficient value after the angle range of 14-18 degrees is achieved at the 60% chord position with the dome vortex, 10.43% increase compared to the baseline lift coefficient. Furthermore, the best value for the lift coefficient after the angle range of 16-18 degrees at the 10% chord position is achieved with the dome vortex, where the maximum lift coefficient 9.4% increase compared to the baseline lift coefficient. It is noted that the baseline configuration consistently outperforms the convergent-divergent vortex configurations.